Universal UX design : building multicultural user experience - Ferreira, Alberto (Elsevier, 2017)
Is there room for culture in an increasingly homogeneous digital experience? Sporting hands-on examples, this book incorporates insights from the latest ethnographic research and market research data, and blends them with key contemporary psychological